2008
DOI: 10.1002/lsm.20713
|View full text |Cite
|
Sign up to set email alerts
|

Role of HSP70 in cellular thermotolerance

Abstract: The data shows that HSP70 contributes significantly to cellular thermotolerance but there are other pathways that provide residual thermotolerance in cells deficient in Hsp70.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 51 publications
2
39
0
Order By: Relevance
“…For example, cells exposed to 45°C for 15 min were observed to undergo transient G 2 block, while when exposed to 45°C for 30 min, they exhibited a long lasting G 2 phase and a late S-phase block [73]. The CSR mechanism is well documented in the literature [66][67][68][69][74][75][76][77], and the general consensus is that cells activate these mechanisms to combat and survive hyperthermic stress. CSR mechanisms involve many intracellular pathways, including redox, DNA sensing and repair, molecular chaperones, proteolysis, energy metabolism, and apoptosis [78].…”
Section: Thermal Effects On Mammalian Cellsmentioning
confidence: 98%
See 1 more Smart Citation
“…For example, cells exposed to 45°C for 15 min were observed to undergo transient G 2 block, while when exposed to 45°C for 30 min, they exhibited a long lasting G 2 phase and a late S-phase block [73]. The CSR mechanism is well documented in the literature [66][67][68][69][74][75][76][77], and the general consensus is that cells activate these mechanisms to combat and survive hyperthermic stress. CSR mechanisms involve many intracellular pathways, including redox, DNA sensing and repair, molecular chaperones, proteolysis, energy metabolism, and apoptosis [78].…”
Section: Thermal Effects On Mammalian Cellsmentioning
confidence: 98%
“…These proteins, collectively referred to as minimal stress proteins, are significantly upregulated by cells immediately after exposure to stress. The most widely studied family of minimal stress proteins are the heat shock proteins (Hsps), which includes Hsp70, Hsp40, Hsp60, and Hsp105 [66][67][68][69][74][75][76][77] (Fig. 4a, c).…”
Section: Thermal Effects On Mammalian Cellsmentioning
confidence: 99%
“…It was found that the Hsp70 expression, as indicated by the reporter gene, contributes significantly to cellular thermotolerance. 13 However, extremely short durations, corresponding to thermal confinement times (on the order of microseconds), were not evaluated.…”
Section: Pulse Duration Determines Levels Of Hsp70 Induction In Tissumentioning
confidence: 99%
“…Increased expression of Hsp70 protects proteins from the damaging effects of stress [45,46]. This has been observed in several types of tumours, including breast and cervical cancers [33,47], and its mechanism may be involved in cell proliferation, prognosis, and drug resistance [26,48,49].…”
Section: Introductionmentioning
confidence: 96%